2020
DOI: 10.1177/8755122520930288
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Clinical Decision-Support Tool on Venous Thromboembolism Prophylaxis in Acutely Ill Medical Patients

Abstract: Background: Adherence to guideline-based venous thromboembolism (VTE) prophylaxis recommendations is often inadequate. Effective improvement strategies are needed. Objective: The purpose of this quality improvement initiative was to increase use of the facility’s preferred pharmacologic VTE prophylaxis, reduce unnecessary VTE prophylaxis use, and reduce use of pharmacologic VTE prophylaxis in high bleeding risk patients, in accordance with guideline-based recommendations. Methods: Clinical pharmacists spearhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
3
2
0
Order By: Relevance
“…This nding was quite unexpected that the CDSS for recommendation VTE prophylaxis within the CPOE system has not affected ICU mortality rate and ICU length of stay. These results consist with other studies which have shown that CDSS for recommendation VTE prophylaxis within CPOE system improves tailored prophylaxis order in nonsurgical patients without effect on patient outcome (18, 30,35). An important implication of this nding is that an electronic CDSS for recommendation VTE prophylaxis within CPOE System can improve appropriate prophylaxis without effects on patient outcome.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This nding was quite unexpected that the CDSS for recommendation VTE prophylaxis within the CPOE system has not affected ICU mortality rate and ICU length of stay. These results consist with other studies which have shown that CDSS for recommendation VTE prophylaxis within CPOE system improves tailored prophylaxis order in nonsurgical patients without effect on patient outcome (18, 30,35). An important implication of this nding is that an electronic CDSS for recommendation VTE prophylaxis within CPOE System can improve appropriate prophylaxis without effects on patient outcome.…”
Section: Discussionsupporting
confidence: 87%
“…Also, the main nding indicates that the CDSS for recommendation VTE prophylaxis within the CPOE system improves clinician adherence to VTE prophylaxis guidelines in nonsurgical patients at ICU. These results agreed with other studies which have shown that VTE prophylaxis CDSS for recommendation prophylaxis order set within CPOE system can improve appropriate VTE prophylaxis in nonsurgical patients at ICU, but the incidence of adherence to VTE prophylaxis guideline is a variety from country to country (29)(30)(31)(32)(33). In contrast to some reports in the literature, Eijgenraam and their colleagues found that after the introduction of VTE prophylaxis CDS did no signi cantly improve adherence in guideline VTE prophylaxis in nonsurgical patients (34).…”
Section: Discussionsupporting
confidence: 85%
“…This nding was entirely unexpected that the CDSS for recommendation VTE prophylaxis within the CPOE system had not affected ICU mortality rate and ICU length of stay. These results consist of other studies showing that CDSS for recommendation VTE prophylaxis within the CPOE system improves tailored prophylaxis orders in nonsurgical patients without affecting the patient outcome [18,30,36,37]. An important implication of this nding is that an electronic CDSS for recommendation VTE prophylaxis within the CPOE System can improve appropriate prevention without affecting patient outcomes.…”
Section: Discussionsupporting
confidence: 67%
“…These results agreed with other studies showing that VTE prophylaxis CDSS for recommendation prophylaxis order set within the CPOE system can improve appropriate VTE prophylaxis in nonsurgical patients at ICU. Still, the incidence of adherence to VTE prophylaxis guidelines is a variety from country to country [29][30][31][32][33]. In contrast to some reports in the literature, Eijgenraam and their colleagues found that after the introduction of VTE prophylaxis, CDS did not signi cantly improve adherence in guideline VTE prophylaxis in nonsurgical patients [34,35].…”
Section: Discussionmentioning
confidence: 94%
“…Per the VA Tennessee Valley Healthcare System (TVHS)-Nashville/Murfreesboro anticoagulation policy, we limit the ordering of parenteral anticoagulation to Computerized Patient Record System (CPRS) order sets in order to provide decision support (eFigure 1, available at doi:10.12788/fp.0063). Other fa-cilities have shown that embedded clinical decision support tools increase adherence to guideline VTE prophylaxis recommendations within the VA. 14 In April 2020, the TVHS anticoagulation clinical pharmacy leads developed a COVID-19 specific order set based on review of societal guidance and the evolving, supportive literature summarized in this review with consideration of provider familiarity (eFigure 2, available at doi:10.12788/fp.0063)). Between April and June 2020, the COVID-19 order set content consistently evolved with publication of each COVID-19 thromboprophylaxis guideline.…”
Section: Covid-19 Thromboprophylaxismentioning
confidence: 99%